Active mobility in an Italian city: Mode choice determinants and attitudes before and during the Covid-19 emergency. (May 2021) - Scorrano, Mariangela; Danielis, Romeo
Abstract: The paper investigates the choice of the transport mode to access the city center of Trieste, Italy. We have collected revealed and stated choice data and attitudinal data in order to investigate the mode of transport used before and during the Covid-19 pandemic. We studied the main choice determinants jointly with respondents' psychological attitudes using an integrated choice/latent variable modelling framework. The model incorporates choice data, generalized cost variables, random parameters, and latent variables. The latter capture the concern for the environment, both at global and local level, the attitudes towards physical exercise and the Covid-19-related risks. The model is applied to assess the impact of extending the density of the cycling lanes on active mobility. Our estimates indicate a potential increase in cycling which, however, would not translate into an increase in active mobility, since the bike would substitute some trips currently made by foot. We also detect a high substitutability between the bike and the bus, while the motorcycle and the car are much less affected. It is confirmed that the Covid-19 pandemic altered significantly the transport mode choices, having a strong negative impact on bus and shifting bus users towards private modes, both motorized and non-motorized. Highlights: We analyze mode choice to access the city center of Trieste. We estimate revealed-stated choices with random parameters hybrid logit models. We investigate attitudes towards the global and local environment, physical exercise and Covid-19. More cycling lanes increase bike use but at the expense of walking and bus use.